Music and Sound in Time Processing of Children with ADHD - Carrer, Luiz Rogério Jorgensen (Frontiers in Psychiatry, 2015)
ADHD involves cognitive and behavioral aspects with impairments in many environments of children and their families’ lives. Music, with its playful, spontaneous, affective, motivational, temporal and rhythmic dimensions can be of great help for studying the aspects of time processing in ADHD. In this article we studied time processing with simple sounds and music in children with ADHD with the hypothesis that children with ADHD have a different performance when compared with children with normal development in tasks of time estimation and production. The main objective was to develop sound and musical tasks to evaluate and correlate the performance of children with ADHD, with and without methylphenidate, compared to a control group with typical development. The study involved 36 participants age 6 to 14 years, recruited at NANI-Unifesp/SP, sub-divided into three groups with 12 children in each. Data was collected through a musical keyboard using Logic Audio Software 9.0 on the computer that recorded the participant's performance in the tasks. Tasks were divided into sections: spontaneous time production, time estimation with simple sounds and time estimation with music. Results: 1. Performance of ADHD groups in temporal estimation of simple sounds in short time intervals (30 ms) were statistically lower than control group (p<0,05); 2. In the task comparing musical excerpts of the same duration (7s), ADHD groups considered the tracks longer when the musical notes had longer durations, while in the control group, the duration was related to the density of musical notes in the track. The positive average performance observed in the three groups in most tasks perhaps indicates the possibility that music can, in some way, positively modulate the symptoms of inattention in ADHD.